Pengaruh Jumlah Tenaga Kerja, Bahan Baku, Dan Teknologi Terhadap Produksi Industri Furniture Di Kota Denpasar - Prianata, Rahadian; Natha, Ketut Suardikha (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 1, Januari 2014 (pp. 1 - 47), 2014)
Normal 0 false false false EN-US X-NONE X-NONE The development of a regional development is a process to raise the level of welfare of society. Another reason why the economic growth and development is undertaken is to be able to stimulate sectors of the economy that is growing, one of which is the industrial sector. The industrial sector is one of the few other sectors are growing rapidly in the area of ??Denpasar. One industry that is growing and is now pretty much in demand is the furniture industry. This research was conducted in the city of Denpasar is divided in 4 districts which aims to determine the effect of the amount of labor, raw materials, and technology and simultaneous partial towards industrial production of furniture in Denpasar. In this study using the entire furniture industry is located in Denpasar are listed in the Department of Industry and Trade number 94 businessmen, divided into 4 districts in the city of Denpasar. This study used multiple linear regression techniques. From the research results obtained by amount of labor, raw materials, and technology affect the industrial production of furniture in Denpasar, and the result obtained by partial amount of labor, raw materials, and technology has a positive effect on the production of the furniture industry in Denpasar city.
Keywords: Number of Labor; Raw Materials; Technology; Industrial Production Furniture